Subclinical cardiovascular remodelling in HIV-infection: a multimodal descriptive study of two serodiscordant, monozygotic twins - Robbertse, Pieter-Paul Strauss; Steyn, Jan; Rajah, Megan; Doubell, Anton; Nachega, Jean; Herbst, Philip (SA Heart Journal, 2024)
Cardiovascular abnormalities have been demonstrated in people living with HIV at the time of HIV diagnosis, but pathology may be challenging to diagnose in the individual. To describe subtle cardiovascular remodelling and dysfunction in two identical twins, one without HIV and the other with a new diagnosis of HIV (serodiscordant). We hypothesise that a difference in cardiovascular parameters would not be demonstrable between the twins, unless non-genetic (environmental) factors were influencing the cardiovascular system. Significant cardiovascular differences likely represent occult pathology secondary to the effects of early HIV-infection, before the initiation of antiretroviral therapy. A 25-year-old female, incidentally diagnosed with HIV (CD4 count 513 cells/ml; estimated time of HIV infection 7-months), underwent cardiovascular magnetic resonance imaging, cardiac biomarker evaluation, and echocardiographic strain assessment. Her healthy, HIV-uninfected identical twin, living together since birth, underwent an identical assessment for comparison. Blinded measurements were performed.